Nota prévia sobre a escavação do sambaqui do porto Maurício - Rauth, José Wilson (Instituto Brasileiro de Informação em Ciência e Tecnologia, 2022)
The Porto Maurício Shellmound is located 5 km away from the bay of Paranaguá and about 100 m. of Rio das Pedras. The excavation was made by square and artificial 25 in. levels, and the natural stratigraphy was recorded.